Pemahaman dan Kesiapan Insinyur Teknik Sipil dalam Green Infrastructure - Saepurrahman, Dewa; Siregar, Chandra Afriade; Pratiwi, A. Andini Radisya; Zamani, Ahmad Fikri; Jainudin, E.; Satria, Eka; Rahayu, Ila; Lestari, Santi Dwi; Gustian, Arif; Iqbal, Rizky; Chalid, Abdul (TECHNO-SOCIO EKONOMIKA, 2025)
Climate change, driven by rising greenhouse gas emissions, significantly impacts our planet. The construction sector, a major contributor to these emissions, demands a shift towards sustainable building practices. Green infrastructure (GI) offers a promising solution by integrating environmental principles into design and construction. This research investigates the understanding, challenges, and readiness of civil engineering graduates in implementing GI. Utilizing a survey-based approach with master's students at Sangga Buana University, the study analyzed the perceptions of students from different backgrounds: Civil Engineering, Other Engineering, and Non-Engineering. Results indicate that Civil Engineering students demonstrate a higher level of awareness and understanding of GI, influenced by their curriculum's focus on sustainable infrastructure development. However, challenges such as cost constraints and limited managerial support persist. Despite these challenges, civil engineering graduates exhibit a greater readiness to embrace and implement GI concepts.